SOCIETY IN J.R.R. TOLKIEN’S TRILOGY THE LORD OF THE RINGS - Dania B. Munder, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Through literature, people learn about various people and societies at contrasting times. Writers have continually explored the importance of books in revealing a man’s race and the entire world of humankind. Furthermore, it shows the thoughts and feelings of writers of their times. This study utilized descriptive research using Tolkien’s The Lord of the Rings as corpus of the study. The literary elements, the kind of society, and generalizations about the society portrayed in the trilogy were analysed using Sociocultural and Marxist theories. The society portrayed in the trilogy is communal, but it gradually shifts to associational because of the effects of the main character’s journey. It also portrays a regionalist society with its unique practices, rules, and languages. Furthermore, this trilogy includes various settings that aid in scrutinizing the kind of society it portrays like the Shire, which can be described as a communal society that shows personal and intimate interactions. Industrialization is correspondingly seen in some associational societies caused by alienation among members of the society that later resulted in a slow cultural extinction. Regionalism is also presented with the inclusion of different races, cultures, languages, and practices. With these, some generalizations concluded consist of the nature of humans to want power and the tendency to be greedy, true love, and loyalty among friends, the unification of different races, and the triumph of goodness against evilness, and the effects of war in society. Finally, the trilogy shows that anyone can grow and learn from their experiences to realize their full potential through interaction in society.